PENGARUH MODAL USAHA, PROMOSI DAN MANAJEMEN USAHA TERHADAP KEBERHASILAN USAHA PADA UMKM DI KABUPATEN MAMUJU - Abdul Wahab; Razak, Mashur; Hidayat, Muhammad (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2024)
This study aims to analyze (1) The partial influence of business capital, promotion, and business management on the success of SMEs in Mamuju Regency. (2) The simultaneous influence of business capital, promotion, and business management on the success of SMEs in Mamuju Regency. (3) The most dominant variable affecting the success of SMEs in Mamuju Regency. This research approach uses a quantitative method. The research was conducted on SMEs in Mamuju Regency and was carried out from November to December 2022. The research population is 50 SMEs. The sample selection in this research was done using a saturated sampling method. The analysis technique used is multiple linear regression analysis. The results show that (1) Partially, business capital, promotion, and business management variables has a positive and significant effect on the success of SMEs in Mamuju Regency. (2) Simultaneously, business capital, promotion, and business management variables has a positive and significant effect on the success of SMEs in Mamuju Regency. (3) The business management variable is the most dominant variable affecting the success of SMEs in Mamuju Regency..